Wokół nowoczesnych konsekwencji romantyzmu w polskiej historiografii - Wenta, Jarosław (Litteraria Copernicana, 2008)
Author’s ambition is arousing interest of forms of reception of the Middle Ages, which there are in scientific literature, popular lecture and general, social awareness. From the title of this paper it appears that a starting point for consideration of tendencies present in polish modern historiography (for such I consider the historiography of the latter part of XX and the beginning of XXI) should be some consequences of the late polish Romanticism: with attempts of revision but also with acceptance of its critical scientific achievements. A model of history made in the nineteenth century in Galicia under the influence of a romantic vision of the polish past may be treated as a moderately coherent entirety. In this model an idea of primitive Slavic control of commune, an opinion of strangeness of the state system or feudal were of paramount importance. Literary (romantic but also modernized e.g. semkowiczowska) visions of Prepiast, ancestral Slavic, archaized and stylized according to notions of Slavic civilization as younger (it is one of elements of romantic view on history accepted strangely enough also by polish historical neo- and postromantics), with an integral element of German danger became a part of polish, universal, historical thinking and historical education.